Sosialisasi Dan Praktek Pemberdayaan Masyarakat Dalam Pembuatan Sirup Jahe Pada Dasawiswa Melati Sumberanyar Banyuputih Situbondo - Andina Mayangsari; Angga Kurdiansyah; Moch Imam Vickry Musthofa (Jurnal Kabar Masyarakat, 2024)
The ginger plant has an important role in the development of health in Indonesia, both as a preventive and promotive approach to maintaining health. This plant is a type of rhizome that is easy to cultivate and is widespread in Indonesia. Apart from being used as a spice and cooking spice, ginger is also an important commodity in industry, especially in the production of ginger powder and syrup. One example of the activities carried out is the socialization of ginger making in Ranurejo Hamlet, Sumberanyar Village, Banyuputih District, Situbondo Regency, East Java Province, which is specifically aimed at women of Dasawiswa Melati Rt.002 Rw.001. The method applied in this activity is participatory, where participants are directly involved in its implementation. The entire socialization process went smoothly, with participants showing high enthusiasm and activeness in participating in this activity.